Light microscopic investigations on the fundic mucosa of rabbit stomach at prenatal and postnatal periods - Mine Yaman; Aydın Girgin (Eurasian Journal of Veterinary Sciences)
In this study. 20 female and 4 male New Zealand Albino rabbits, their fetuses and newborns were used. The rabbits were sacrificied and the tissue samples were taken from fundus of stomach and processed (or light microscopic investigations. At the 19 th day of prenatal period mucosal epithelial layer surrounding the central lumen displayed stratified structure and surface of mucosa itself displayed a rough course. Also, at the 21st day of prenatal period, mucosal surface was irregular and the epithelium consisted of 2-3 cell layers. At the 23 rd day of fetal period the mucosal epithelium was stratified and developing primary glands were first observed at this period. At the 27 th day of the fetal period, epithelium had simple columnar structure. At the 29 th day of fetal period, the mucosal surface was covered with a thin mucus layer which was strongly positive for alcian blue. On the 1 st day of postnatal period, fundic mucosa continued its development and by the 20 day it has gained its mature structure.